W domu i na pensji – dziewczęce zapiski i kobiece wspomnienia o edukacji z końca XVIII wieku - Żołądź-Strzelczyk, Dorota; Kowalczyk, Małgorzata Ewa (Biuletyn Historii Wychowania, 2024)
Women’s opportunities to acquire knowledge and skills in the 18th century still differed significantly from men’s. Girls had fewer choices: education at home, or at a finishing school. It was mainly convent education, over time giving way to secular education. This article attempts to show education from the perspective of women, their memories recorded in diaries. Two of them were selected for this purpose. The author of the first, Wirydianna Fiszerowa, née Radolińska, described and evaluated her home education retrospectively. She showed a lack of consistency and a thoughtful approach, frequent changes of teachers, whom she sometimes assessed in a decidedly negative way, the teaching and upbringing methods they used. The other girl, Apolonia Helena Massalska, while studying at a convent finishing school, wrote down her diary on a regular basis, showing the life of her peers, her relations with the teachers and their educational methods. In the first case, the author could distance herself after several decades and life experience; she included a reflection on the scope and method of providing education. This second diarist, inevitably deprived of distance, basically limited herself to describing life and teaching at the finishing school.